Isolation of Novel Probiotic Lactobacillus and Enterococcus Strains From Human Salivary and Fecal Sources - Bazireh, Homa; Shariati, Parvin; Azimzadeh Jamalkandi, Sadegh; Ahmadi, Ali; Boroumand, Mohammad Ali (Frontiers in Microbiology, 2020)
Probiotics are non-pathogenic microorganisms that can interact with the gastrointestinal microbiota. They have numerous beneficial health effects that include enhancement of the host immune response, antiallergic, antimicrobial, anti-cancer, and anti-inflammatory properties. Probiotics are capable of restoring the impaired microbiome of a dysbiotic gut. They can be isolated from different environments. However, it is frequently suggested that probiotics for human use should come from human sources. The objective of this study was to isolate and characterize novel probiotic strains from the saliva and feces of healthy human individuals. To meet the criteria for probiotic attributes, the isolates were subjected to numerous standard morphological and biochemical tests. These tests included Gram staining, catalase tests, antibiotic susceptibility testing, hemolytic and antagonistic evaluation, tolerance tests involving temperature, NaCl levels, pH and bile salts, adherence ability assays, and genotypic characterization involving 16S rRNA gene sequencing. From 26 saliva and 11 stool samples, 185 microbial strains were isolated. Based on morphological and biochemical characteristics, 14 potential probiotic candidates were selected and identified genotypically. The new strains belonged to Lactobacillus fermentum, Enterococcus faecium, and Enterococcus hire. The selected strains were non-hemolytic, showed high tolerance to low pH and bile salts, and strong adherence abilities. Furthermore, the strains displayed a wide range of antimicrobial activities, particularly against antibiotic-resistant pathogens such as methicillin resistant Staphylococcus aureus (MRSA). Moreover, five of the selected isolates demonstrated antiproliferative features against human colon cancer cell line (Caco-2). The results of this investigation confirm the diversity of microbial populations in the human gut and saliva, and since these strains are of human origin, they will highly likely display maximal activities in food and drugs set for human use. Hence, the new strains of this study require additional in vivo experiments to assess their health-promoting effects.